2014
DOI: 10.1038/mt.2013.255
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy-induced CD8+ T Cells Instigate Immune Suppression in the Tumor

Abstract: Despite clear evidence of immunogenicity, cancer vaccines only provide a modest clinical benefit. To evaluate the mechanisms that limit tumor regression following vaccination, we have investigated the weak efficacy of a highly immunogenic experimental vaccine using a murine melanoma model. We discovered that the tumor adapts rapidly to the immune attack instigated by tumor-specific CD8+ T cells in the first few days following vaccination, resulting in the upregulation of a complex set of biological networks, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 46 publications
5
54
0
Order By: Relevance
“…In this study, we show greater antitumor effects when combining pathogenbased cancer vaccine with ACT of dual-specific CD8 T cells than recombinant Listeria expressing a tumor antigen. This result can be explained by a greater magnitude of clonal expansion of adoptively transferred tumor-specific CD8 T cells than that from endogenous T cells, which supports the idea that the initial T-cell-mediated killing crucially depends on sufficiently high doses of T cells within the tumor for successful eradication (26).…”
Section: Discussionsupporting
confidence: 64%
“…In this study, we show greater antitumor effects when combining pathogenbased cancer vaccine with ACT of dual-specific CD8 T cells than recombinant Listeria expressing a tumor antigen. This result can be explained by a greater magnitude of clonal expansion of adoptively transferred tumor-specific CD8 T cells than that from endogenous T cells, which supports the idea that the initial T-cell-mediated killing crucially depends on sufficiently high doses of T cells within the tumor for successful eradication (26).…”
Section: Discussionsupporting
confidence: 64%
“…Unfortunately, current preclinical animal models do not allow us to study this possibility in the context of adoptive Tcell transfer. Many previous studies combining virotherapy and ACT have focused on oncolytic viruses encoding TAAs, thus relying mostly on oncolysis and vaccination effect against a particular tumor epitope (8,(41)(42)(43). In our hands, the mere adenoviral backbone acted as an adjuvant and boosted the endogenous antitumor immunity elicited by ACT.…”
Section: Discussionmentioning
confidence: 82%
“…Peripheral tolerance of tumor-specific T cells due to insufficient costimulation by professional antigen-presenting cells (APC) may result in T-cell deletion or anergy (7). Furthermore, the highly immunosuppressive TME typically renders infiltrating T cells incapable of killing their target (tumor) cells (8). For successful cancer immunotherapy, the TME has to be immunogenic enough in order to accomplish T-cell-mediated cytolysis and subsequent antitumor responses.…”
Section: Introductionmentioning
confidence: 99%
“…Their accumulation and suppression activity were caused by IFNg produced by the effector CTLs (40). Similarly, a recent report showed that the low efficacy of vaccination in melanoma-bearing mice was associated with IFNg production by early attacking and invading CD8 þ T cells, resulting in the upregulation of immunosuppressive processes that suppressed local Tcell activation (41). In our ex vivo system, we showed that IFNg production by activated CD4 þ T cells was required to sustain the initial activation of M-MDSCs and render functional the M-MDSC:mast cell-suppressive axis.…”
Section: Discussionmentioning
confidence: 99%